Storage moduli, loss moduli and damping factor of GaAs and Ga1-xMnxAs thin films using DMA 2980 - Kemei, S. K.; Kirui, M. S. K.; Ndiritu, F. G.; Odhiambo, P. M.; Ngumbu, R. G.; Leite, D. M. G. [UNESP]; Pereira, A. L. J. [UNESP] (Elsevier B.V., 2014)
The spin injector part of spintronic FET and diodes suffers from fatigue due to rising heat on the depletion layer. In this study the stiffness of Ga1-xMnxAs spin injector in terms of storage modulus with respect to a varying temperature, 45 degrees C <= T <= 70 degrees C was determined. It was observed that the storage modulus for MDLs (Manganese Doping Levels) of 0%, 1% and 10% decreased with increase in temperature while that with MDLs of 20% and 50% increase with increase in temperature. MDLs of 20% and 50% appear not to allow for damping but MDLs <= 20% allow damping at temperature range of 45 degrees C <= T <= 70 degrees C. The magnitude of storage moduli of GaAs is smaller than that for ferromagnetic Ga1-xMnxAs systems. The loss moduli for GaAs were found to reduce with increase in temperature. Its magnitude of reducing gradient is smaller than Ga1-xMnxAs systems. The two temperature extremes show a general reduction in loss moduli for different MDLs at the study temperature range. From damping factor analysis, damping factors for ferromagnetic Ga1-xMnxAs was found to increase with decrease in MDLs contrary to GaAs which recorded the largest damping factor at 45 degrees C <= T <= 70 degrees C Hence, MDL of 20% shows little damping followed by 50% while MDL of 0% has the most damping in an increasing trend with temperature. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Storage modulus; Loss modulus; Damping; Dynamic mechanical analysis; Manganese doping levels